2005
DOI: 10.1111/j.1440-1854.2005.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Home management of childhood febrile illnesses in a rural community in Nigeria

Abstract: The findings indicate home use of drugs that were not prescribed by health professionals. There is therefore a strong need to give appropriate education and counselling to mothers/care givers and medicine vendors on early detection and proper home management of febrile illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 5 publications
4
19
1
Order By: Relevance
“…3 In another study on home management of childhood febrile illnesses in a rural community in Nigeria, one mother out of 200 reported to the clinic within 24 h of child's illness. 4 This trend is in line with the current recommendations encouraging mothers to treat their children suffering from malaria at home. However, the findings in our study show that mothers are not adequately equipped to do so.…”
Section: Discussionsupporting
confidence: 73%
“…3 In another study on home management of childhood febrile illnesses in a rural community in Nigeria, one mother out of 200 reported to the clinic within 24 h of child's illness. 4 This trend is in line with the current recommendations encouraging mothers to treat their children suffering from malaria at home. However, the findings in our study show that mothers are not adequately equipped to do so.…”
Section: Discussionsupporting
confidence: 73%
“…This study also shows that quinine was often prescribed without proper indication. The results of urine assays suggest the reality of self-treatment and the frequent lack of compliance to the treatment, as reported in others studies (Abuya et al, 2005;Olaogun et al, 2005). These results have been communicated to the health authorities to help them improve the training of the medical staff in dispensaries and to try to reduce these treatment misuses.…”
Section: Discussionsupporting
confidence: 68%
“…The link between fever signs, malaria as a cause of pain could account for the high number of mothers that use drug therapy in relieving pain. Studies from many African countries that are malaria endemic have shown that home management is the first action used by primary caregivers in the treatment of febrile conditions in children 25–27 . Drugs used are mainly, analgesics, antipyretic and antimalarials that are usually taken from previous prescriptions or bought from the PMS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from many African countries that are malaria endemic have shown that home management is the first action used by primary caregivers in the treatment of febrile conditions in children. [25][26][27] Drugs used are mainly, analgesics, antipyretic and antimalarials that are usually taken from previous prescriptions or bought from the PMS. It is only when this first action fails that health facilities are used.…”
Section: Discussionmentioning
confidence: 99%